Kemungkinan Adaptive Coping Styles dalam Mencegah Kejadian Depresi pada Mahasiswa selama Pandemi COVID-19: Kajian Pustaka - Rakanda Muhammad Naufal Pratomo; Putri Qintara Choirunnisa; Nugraha Sutadipura; Dede Setiapriagung (UNISBA Press, 2022)
Abstract. The COVID-19 pandemic has caused a bad psychological response in all groups of society, especially young adult university students. This is because there are stressors that come from the environment, such as someone who is separated from his family, lives in a place that is prone to COVID-19 transmission, or face-to-face learning turns into online learning. These stressors can cause psychological symptoms, namely depression. Major Depressive Disorder (MDD) or depression is a mood disorder that is chronic and can spread, characterized by persistently low mood, hopelessness, anhedonia, loss of energy, and cognitive dysfunction. There are discrete episodes lasting at least 2 weeks that can produce marked changes in effects on cognition, neurovegetative function, and interepisode remission. Depression is caused by reduced expression of the NR3C1; methylation of the BDNF gene; methylation of the SLC6A4 promoter. Psychosocially caused by developmental predisposition and life events. As many as 1 in 5 groups of young adults suffer from depression and about 6.2% want to commit suicide. Adaptive coping styles play a role in intervening these mechanisms in the medial prefrontal cortex and nucleus accumbens. Thus, stressors can be handled properly and can prevent symptoms of depression in university students during the COVID-19 pandemic. Abstrak. Pandemi COVID-19 menimbulkan respons psikologis yang buruk pada semua kelompok masyarakat, terutama kelompok mahasiswa usia dewasa muda. Hal tersebut disebabkan karena terdapat stresor yang berasal dari lingkungan, seperti seseorang yang terpisah dengan keluarga, tinggal ke tempat yang rentan adanya penularan COVID-19, atau pembelajaran tatap muka berubah menjadi pembelajaran dalam jaringan (daring). Stresor tersebut dapat menyebabkan gejala psikologis, yaitu depresi. Major Depressive Disorder (MDD) atau depresi adalah gangguan mood yang bersifat kronis dan dapat menyebar, ditandai dengan mood yang terus-menerus rendah, putus asa, anhedonia, kehilangan energi, dan disfungsi kognitif. Terdapat episode diskrit paling tidak selama 2 minggu yang dapat membuat perubahan jelas dalam pengaruh pada kognisi, fungsi neurovegetative, dan remisi interepisode. Depresi disebabkan oleh ekspresi gen NR3C1 yang berkurang; methylation pada gen BDNF; methylation pada SLC6A4 promoter. Secara psikososial disebabkan oleh developmental predisposition dan life events. Sebanyak 1 dari 5 kelompok dewasa muda menderita depresi dan sekitar 6,2% ingin bunuh diri. Adaptive coping styles berperan dalam mengintervensi mekanisme tersebut pada medial prefrontal cortex dan nucleus accumbens, sehingga stresor dapat ditangani dengan baik dan dapat mencegah gejala depresi pada mahasiswa selama Pandemi COVID-19.